The role of ethnoscience in the build-up of ethnoconservation as a new approach to nature conservation in the tropics - Antonio Carlos Diegues (Revue d'ethnoécologie)
This paper aims to describe the main features of a new approach in nature conservation in the Tropics and to analyse the important role of ethnoscience in this process, taking Brazil as a case study.It begins with a critique of the hegemonic model for nature conservation in which traditional communities living in the areas transformed into non-use protected areas have been displaced or too severely hindered to continue with their traditional way of life based on small-scale agriculture, fishing, forest harvesting and hunting. The role of big international conservation NGOs in spreading this hegemonic approach in developing countries is also analysed.This model is being set-up in many tropical countries. It consists in recognizing the rights of traditional communities to their territories, using traditional knowledge, encouraging people to participate and ensuring the cooperation between natural and social sciences in the process of nature management.